Health risk behaviours among migrants by duration of residence: protocol for a systematic review and meta-analysis - Berg, Lisa (BMJ Open, 2020)
INTRODUCTION: International migrants’ health has often been found to deteriorate in new countries, partly due to changes in health risk behaviours such as alcohol consumption, tobacco use, physical inactivity, and poor dietary habits. However, limited efforts have been made to comprehensively evaluate the extent to which migrants adopt unhealthy risk behaviours with longer duration of residence. This systematic review and meta-analysis will summarise evidence on international migrants’ behavioural patterns by duration of residence in multiple country contexts. METHODS AND ANALYSIS: PubMed/MEDLINE, Web of Science and ProQuest databases will be searched for quantitative or mixed-method observational studies published in peer-reviewed scientific journals between 1 January 2000 and 31 December 2019. Studies comparing foreign-born individuals by duration of residence will be included. Information on study characteristics, descriptive statistics and measures of effect will be extracted. All included studies will be quality assessed using a modified Newcastle-Ottawa scale. The review will include narrative synthesis and, if sufficient and comparable data are available, random effects meta-analyses. The review will be conducted in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. ETHICS AND DISSEMINATION: Ethical approval is not required since previously published information from peer-reviewed studies will be assessed. The results of this review will be published in peer-reviewed journals and presented at scientific conferences. Other forms of dissemination will include communication to broader audiences using well-established channels, including through university-based press releases. Progress will be regularly updated on the International Prospective Register of Systematic Reviews to ensure full transparency. PROSPERO REGISTRATION NUMBER: CRD42018108881